2021
DOI: 10.12688/f1000research.54864.1
|View full text |Cite
|
Sign up to set email alerts
|

The need to reassess single-cell RNA sequencing datasets: more is not always better

Abstract: Background: The advent of single-cell RNA sequencing (scRNAseq) and additional single-cell omics technologies have provided scientists with unprecedented tools to explore biology at cellular resolution. However, reaching an appropriate number of good quality reads per cell and reasonable numbers of cells within each of the populations of interest are key to infer conclusions from otherwise limited analyses. For these reasons, scRNAseq studies are constantly increasing the number of cells analysed and the granu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Reassessment of the main cell populations in a large skin dataset reveals the presence of clusters with stress-and hypoxia-related gene signatures By using an unsupervised population-matching algorithm (details in processed notebooks available online 20 ) we observed that in each of the healthy donors analysed by Reynolds et al, 13 at least two independent fibroblast clusters expressed signature markers of the A1, A2, B1 and B2 populations. One set of cells corresponded to the Fb2 population, and the second set corresponded to the Fb1 and Fb3 populations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reassessment of the main cell populations in a large skin dataset reveals the presence of clusters with stress-and hypoxia-related gene signatures By using an unsupervised population-matching algorithm (details in processed notebooks available online 20 ) we observed that in each of the healthy donors analysed by Reynolds et al, 13 at least two independent fibroblast clusters expressed signature markers of the A1, A2, B1 and B2 populations. One set of cells corresponded to the Fb2 population, and the second set corresponded to the Fb1 and Fb3 populations.…”
Section: Resultsmentioning
confidence: 99%
“…Processed notebooks and AnnData files can be found at: https://doi.org/10.5281/zenodo.4596374. 20 License: Creative Commons Attribution 4.0 International.…”
Section: Data Availabilitymentioning
confidence: 99%
“…In this case, fibroblast subpopulations were characterized by the expression of signature genes COL1A1 and COL1A2, CXCL12, and CCL19, respectively [40]. Of note, a preprint posting a reanalysis of this study postulates that their fibroblast clustering is unreliable due to technical reasons [33].…”
Section: Single-cell Analyses Of Fibroblastsmentioning
confidence: 99%
“…Of all solid tissues, the study of skin has gained traction in the single-cell community because it is accessible and read-ily available. However, skin disaggregation-as with any other solid tissue-presents some technical challenges, and this will impact cell viability, as well as the representativeness of the obtained sample [32,33]. To date, most of the single-cell studies on healthy skin are focused either on determining the heterogeneity of fibroblasts from the dermis or understanding transcriptional changes underlying the differentiation of keratinocytes in the interfollicular epidermis.…”
Section: Single-cell Analysis Of Healthy Skinmentioning
confidence: 99%
See 1 more Smart Citation